2020
DOI: 10.33422/ijarme.v3i4.508
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Customer Loyalty in Telecommunication Sector

Abstract: Customer loyalty is a serious matter of concern for every business where it measures the customer’s likeliness to give repeat business with a brand or organization. In other words, it is the outcome of a positive experience for customers as well as customer satisfaction. In this paper, the role of the relational dimension will be studied in the context of customer loyalty. The aim of this paper is to analyze the concept of relationship marketing and the key variables of the dimension relationship and their rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Customer loyalty can be supported by the self-determination theory (Ntoumanis 2005) and the expectation-confirmation theory which is generally used to study customer satisfaction, and loyalty (Bhattacherjee 2001). Past studies have identified determinants such as service quality, trust, corporate image, and switching costs that are positively and significantly related to customer loyalty among female consumers (Singh, 2020). One of the strategies used by businesses is loyalty programs.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…Customer loyalty can be supported by the self-determination theory (Ntoumanis 2005) and the expectation-confirmation theory which is generally used to study customer satisfaction, and loyalty (Bhattacherjee 2001). Past studies have identified determinants such as service quality, trust, corporate image, and switching costs that are positively and significantly related to customer loyalty among female consumers (Singh, 2020). One of the strategies used by businesses is loyalty programs.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…There are numerous studies available on customer loyalty (Hapsari et al, 2020;Singh, 2020;Ting et al, 2020). But there is a need to resolve the dilemma related to the importance of the factors that have been explored in the previous studies.…”
Section: Introductionmentioning
confidence: 99%